The effect of different cooking techniques of oyster mushroom on physicochemical and sensory properties and its application in beef patty - Fadzil, Rifhan Aqilah Mohammad (Universiti Sains Malaysia, 2015)
The inheritance of Malaysian food is frequently driven by international influences which cause Malaysia to rely on imports of red meat. The utilization of non-meat-based substitute such as mushroom to the patty formulation is potentially practical since it contain various nutritive values. The effect of different cooking techniques on physical and sensory properties of oyster mushroom and its application in beef patty were investigated. Result shows beef patty replaced with raw oyster mushrooms (control), recorded the highest cooking yield (85.40%). On the other physical traits, beef patty which was replaced with blanched oyster mushroom (BOM), recorded the highest moisture retention (33.32%). The color analysis of beef patty substitute with 25% of steamed oyster mushrooms (SOM) was brighter as it had higher L* (lightness) value compared with raw beef patty substitute with BOM but less brightness compared to the control patty. Beef patty substituted with BOM recorded the lowest a* value (redness) compared to beef patty substituted with SOM and control, respectively. Meanwhile, beef patty substituted with SOM recorded the highest b* value (yellowness) compared to beef patty substituted with BOM and control, respectively. Sensory evaluation of the products revealed significant (p<0.05) differences for color, juiciness, flavor, overall acceptance attributes. Conversely, the products had no significant (p>0.05) effect on aroma and tenderness attributes. The score for color of beef patty substituted with SOM was not significantly different (p>0.05) from the control. In summary, different cooking techniques applied to the oyster mushroom before substituted in the beef patty did not jeopardize several physical properties and sensory properties attributes.